Genetic diversity and morphological variability of Iranian Silene aucheriana populations inferred from nrDNA ITS sequences and morphological analysis - Safaeishakib, Masoumeh; Assadi, Mostafa; Ghazanfar, Shahina A.; Mehregan, Iraj (Hacquetia, 2023)
We conducted a comprehensive study on the diversity of Silene aucheriana Boiss. populations by analyzing both morphological data and nrDNA ITS sequences. Maximum parsimony and Bayesian methods on representative material from 15 populations throughout Iran demonstrated that they did not form a monophyletic group. Strong positive correlation occurred between epipetalous filaments length to claw (EFLC), basal leaf length (BLL), basal leaf width (BLW), and plant height (PLH) with elevation. While negative correlation achieved between anthophore length (AnL) with the average air temperature and rainfall. Canonical Correspondence Analysis (CCA) showed that most morphological traits were more correlated to elevation than to average rainfall and temperature. Multivariate analysis of morphological traits with ITS analysis displayed a slight divergence between two types of regions based on their elevation.